Empowering Perlis Tabika Kemas through locally-developed language activities program - Osman, Nazira; Chulan, Majdah; Rosaidi, Nor Alifah; Abdul Pisal, Nadhilah; Noor, Noorzilah (Universiti Teknologi MARA, Kedah, 2024)
English is the second most important language, but yet many Malaysians face difficulties acquiring it. Some believe that this is because the citizens did not learn it well when they were young. It should thus be interestingly taught, especially to preschoolers, so that it will not be difficult for them to be proficient in the language as they get older. Realising this fact, the program Empowering Perlis Tabika KEMAS through Locally-Developed Language Activities was carried out by Akademi Pengajian Bahasa, Universiti Teknologi MARA (UiTM) Perlis Branch in collaboration with Jabatan Kemajuan Masyarakat (KEMAS) Perlis. The project was aimed at sharing knowledge with Tabika KEMAS teachers on the use of English materials that have local content and to help them improve the teaching and learning of the English language to young children (age 4-6 years old). This community project has undergone two (2) phases: training workshops and observation. The participants include 42 teachers and 53 children from three (3) selected Tabika KEMAS around Arau Parliament of Perlis. The project's outcomes demonstrated a better understanding of teaching English among teachers and how they successfully implemented locally-developed language activities with their students in the classroom. It also gives a fresh new experience to the teachers and enhances their motivation in using creative and fun language activities with the children of Tabika KEMAS.